2022
DOI: 10.1002/joc.7507
|View full text |Cite
|
Sign up to set email alerts
|

Impact of North Atlantic Oscillation and drought conditions on summer urban heat load ‐ a case study for Zagreb

Abstract: Frequent heat waves in the latest decade have drawn attention due to large mortality and economic losses. Urban areas are in additional danger of extreme heat due to the well-known urban heat island (UHI) phenomena. Here, we investigate the effect of the North Atlantic Oscillation (NAO) in modifying urban heat in Zagreb, Croatia. Both winter (wNAO) and summer (sNAO) NAO components are analysed in terms of indirect (lagged) and direct effects on the urban heat load. The strongest increase in heat load was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Popov et al, 2018b;Nimac et al, 2022) and local studies (Unkaševi c and Toši c, 2013). For example, the strongest and significant correlation with the NAO index is detected for maximum air temperature in Zagreb (Croatia) during the winter and summer seasons (Nimac et al, 2022). Similar results are obtained by Popov et al (2018b) for four meteorological stations in Bosnia and Herzegovina.…”
Section: Discussionmentioning
confidence: 99%
“…Popov et al, 2018b;Nimac et al, 2022) and local studies (Unkaševi c and Toši c, 2013). For example, the strongest and significant correlation with the NAO index is detected for maximum air temperature in Zagreb (Croatia) during the winter and summer seasons (Nimac et al, 2022). Similar results are obtained by Popov et al (2018b) for four meteorological stations in Bosnia and Herzegovina.…”
Section: Discussionmentioning
confidence: 99%
“…The trilinear interpolation yields interpolated fields of air temperature, relative humidity, and wind speed which enable the calculation of the spatial distribution of climate indices. A more detailed description of the MUKLIMO_3 model and the cuboid method can be found in several studies considering urban heat load (Früh et al, 2011;Žuvela-Aloise et al, 2014Žuvela-Aloise et al, , 2016Žuvela-Aloise, 2017;Nimac et al, 2022).…”
Section: Model Muklimo_3 and Model Set Up For Dubrovnikmentioning
confidence: 99%
“…Boras et al (2022) have shown rising trends for mean, minimum and maximum temperatures in the city of Dubrovnik for the period 1961-2020, which are highest during summer months, but they did not investigate future trends of heat load. On the other hand, it has been shown that in different locations in Zagreb, the type of climate has already changed due to increasing air temperatures, and additional temperature increases are expected in the future (Nimac, 2022;Nimac et al, 2022). It is obvious that there is a lack of systematic research focused on the expected heat load of cities in Croatia.…”
Section: Introductionmentioning
confidence: 99%